2014
DOI: 10.20883/medical.e53
|View full text |Cite
|
Sign up to set email alerts
|

The influence of age and dosage on the pharmacodynamics of dexmedetomidine in rabbits

Abstract: Aim. This study aimed to examine the influence of maturation and dosage on the sedative and haemodynamic response observed in rabbits after the administration of dexmedetomidine. Material and methods. The pharmacodynamics of dexmedetomidine was studied on 14 healthy New Zealand white rabbits at three periods of maturation; stage 1–1.5 months old, stage 2–2.5 months old and stage 3–6.5 months old ones. The administered dose of dexmedetomidine ranged from 25 µg/kg to 300 µg/kg of body weight. The pedal withdrawa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…The surgical anesthetic duration was measured using ear pinch reflex and pedal withdrawal reflex, as described in the literature. In adult rabbits, [19,20] found that reflex loss and return periods varied according to the dose of anesthetic regimens, with stronger doses providing longer sedation durations and longer pedal withdrawal reflex return times. The results of this study provide valuable insights into the physiological responses of rabbits undergoing tendon surgery with different anesthesia protocols.…”
Section: Resultsmentioning
confidence: 99%
“…The surgical anesthetic duration was measured using ear pinch reflex and pedal withdrawal reflex, as described in the literature. In adult rabbits, [19,20] found that reflex loss and return periods varied according to the dose of anesthetic regimens, with stronger doses providing longer sedation durations and longer pedal withdrawal reflex return times. The results of this study provide valuable insights into the physiological responses of rabbits undergoing tendon surgery with different anesthesia protocols.…”
Section: Resultsmentioning
confidence: 99%
“…It is known that α2 agonists lead to a noticeable decrease in HR (7,15,18). In addition, it was reported that medetomidine and dexmedetomidine lead to bradycardia irrespective of the route of administration and dose (4,27). On the other hand, it is known that the effect of midazolam at therapeutic doses on the cardiovascular system is minimal (3,14,18).…”
Section: Resultsmentioning
confidence: 99%
“…Cheng Chang et al (9) reported that dexmedetomidine reduced MAP in rabbits and produced more hypotension than midazolam did. Bienert et al (4) reported that dexmedetomidine changed MAP in a dose-dependent manner, and low-dose dexmedetomidine led to a higher reduction in MAP. They observed a relationship in which an increase of 10 µg/kg in the dose of dexmedetomidine led to an increase of 10.3 mmHg in MAP.…”
Section: Resultsmentioning
confidence: 99%
“…When compared to the other groups, group DFK had the longest duration of anaesthesia and the shortest period of loss of righting and palpebral reflex. Karasu et al (2018) and Bienert et al (2014) described that in adults, healthy rabbits' reflex loss and MJAVL Volume 12 (Issue 2) © 2022 www.journals.manas.edu.kg return timings vary according to the dose of anaesthetic regimes, with higher doses resulting in longer sedation durations and longer pedal withdrawal reflex recovery times. The administration of a combination of diazepam, fentanyl, and ketamine may have produced the difference in the periods of loss and recovery of the righting and palpebral reflexes in this investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Gil et al (2004) found a considerable increase in serum chloride levels after DK treatment, which corroborated this finding. Because the kidney is the principal site of excretion of this electrolyte, decreased renal blood flow owing to diazepam could be the source of the higher plasma chloride levels (Bienert et al 2014).…”
Section: Discussionmentioning
confidence: 99%